Chemical Constituents from the Fungus Amauroderma amoiensis and Their In Vitro Acetylcholinesterase Inhibitory Activities - Zhang, Shuang Shuang; Ma, Qing Yun; Zou, Xi Sheng; Dai, Hao Fu; Huang, Sheng Zhuo; Luo, Ying; Yu, Zhi Fang; Luo, Huai Rong; Zhao, You Xing (Planta Medica, 2013)
One new compound named amauroamoienin (1), together with thirteen known compounds (2–14), was isolated from the EtOAc extract of Amauroderma amoiensis. The structures of these compounds were elucidated by the analysis of 1D and 2D spectroscopic data and the MS technique. The bioassays of inhibitory activities of these isolates against acetylcholinesterase were evaluated, and compounds 1, 3, and 5 exhibited acetylcholinesterase inhibitory activities.
Keywords: Amauroderma amoiensis; Ganodermataceae; amauroamoienin; acetylcholinesterase inhibitory activity